Soluble Iodine Speciation in Marine Aerosols Across the Indian and Pacific Ocean Basins - Droste, Elise S.; Baker, Alex R.; Yodle, Chan; Smith, Andrew; Ganzeveld, Laurens (Frontiers in Marine Science, 2021)
Iodine affects the radiative budget and the oxidative capacity of the atmosphere and is consequently involved in important climate feedbacks. A fraction of the iodine emitted by oceans ends up in aerosols, where complex halogen chemistry regulates the recycling of iodine to the gas-phase where it effectively destroys ozone. The iodine speciation and major ion composition of aerosol samples collected during four cruises in the East and West Pacific and Indian Oceans was studied to understand the influences on iodine’s gas-aerosol phase recycling. A significant inverse relationship exists between iodide (I-) and iodate (IO3-) proportions in both fine and coarse mode aerosols, with a relatively constant soluble organic iodine (SOI) fraction of 19.8% (median) for fine and coarse mode samples of all cruises combined. Consistent with previous work on the Atlantic Ocean, this work further provides observational support that IO3- reduction is attributed to aerosol acidity, which is associated to smaller aerosol particles and air masses that have been influenced by anthropogenic emissions. Significant correlations are found between SOI and I-, which supports hypotheses that SOI may be a source for I-. This data contributes to a growing observational dataset on aerosol iodine speciation and provides evidence for relatively constant proportions of iodine species in unpolluted marine aerosols. Future development in our understanding of iodine speciation depends on aerosol pH measurements and unravelling the complex composition of SOI in aerosols.